A Ternary Nickel(II) Schiff base complex containing di-anionic and neutral forms of a dithiocarbazate Schiff base - Enis Nadia Md Yusof,; Nazhirah M Nasri,; Ravoof, Thahira Begum S. A.; Tiekink, Edward R. T. * (MDPI, 2019)
The title NiII complex, Ni(L)(LH2) (1), where LH2 is S-2-methybenzyl-β-N-(2-hydroxy-3-methoxybenzylmethylene) dithiocarbazate, was isolated from the reaction of Ni(acetate)2·4H2O and two molar equivalents of LH2. The complex was characterized by elemental analysis, spectroscopy (IR and UV) as well as by a single-crystal X-ray structure determination. The nickel(II) center is coordinated within a cis-NOS2 donor set that defines a square planar geometry. Three donor atoms, i.e., N, O, and S, are provided by a doubly deprotonated S-2-methybenzyl-β-N-(2-hydroxy-3-methoxybenzylmethylene) dithiocarbazate ligand while the fourth donor, i.e., a thione-S, comes from the neutral form of the dithiocarbazate ligand. In the LH2 ligand, an intramolecular hydroxy-O-H…N(imine) hydrogen bond is found. There is also an intra-ligand, charge assisted amine-N-H…O(phenoxide) hydrogen bond. A notable feature of the molecular packing is the formation of supramolecular chains sustained by π…π stacking interactions whereby the interacting rings are the five- and six-membered chelate and methoxybenzene rings. The chains are connected into a three-dimensional architecture by methyl-C-H…O(methoxy), methoxy-C-H…S(ester), and tolyl-C-H…π(tolyl) interactions.